Evaluation of the True View PCD Video Laryngoscope for Oral Endotracheal Intubation - Neha Agrawal; Alks Shah; Balraj Joshi; Pinal Vasani (Academia Anesthesiologica International, 2020)
Background: Truview PCD video laryngoscope is particularly planned to assist in locating the endotracheal tube in addition to observe the admission of the tube into the glottis. The present study was performed to assess the outlook of glottic opening and relief of intubation between the Truview PCD laryngoscope and Macintosh laryngoscope in patients undergoes general anaesthesia. Subjects and Methods: Ninety patients of ASA grade 1 and 2 aged 18-60 years, posted for elective surgery under general anaesthesia needing endotracheal intubation were arbitrarily allocated into group 1 (Truview PCD laryngoscope n=45) and group 2 (Macintosh laryngoscope n=45). The two groups were compared for demographic data, intubation difficulty score, Cormack-Lehane grade, time to intubate, number of intubation attempts and hemodynamic parameters. Conclusion: Truview PCD can be measured as an alternate intubation device, especially in difficult intubation conditions.